2021
DOI: 10.1186/s40537-020-00406-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep stage classification using extreme learning machine and particle swarm optimization for healthcare big data

Abstract: Recent developments of portable sensor devices, cloud computing, and machine learning algorithms have led to the emergence of big data analytics in healthcare. The condition of the human body, e.g. the ECG signal, can be monitored regularly by means of a portable sensor device. The use of the machine learning algorithm would then provide an overview of a patient’s current health on a regular basis compared to a medical doctor’s diagnosis that can only be made during a hospital visit. This work aimed to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The third reason may be that we did not try to optimize the training and input features. By comparison, Surantha et al [59] selected different features for every sample for staging that achieved an accuracy of 71.52%. This is, however, difficult to implement in practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The third reason may be that we did not try to optimize the training and input features. By comparison, Surantha et al [59] selected different features for every sample for staging that achieved an accuracy of 71.52%. This is, however, difficult to implement in practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative study shown in Table 1 considers various datasets by which the performance varies in terms of accuracy. Hence, the comparison is mainly focused on the postures considered in the initial works considering the off-bed, sitting, lying center, lying left, and lying right, whereby the prone posture is not considered in deep neural networks and K -nearest neighborhood algorithm [ 11 ]. The next important comparison parameter is the number of sensors used.…”
Section: Discussionmentioning
confidence: 99%
“…A low-cost pressure array is embedded with conductive fabric and conductive wires, where sensors are deployed with bedspreads configured as 32 rows and 32 columns with a total of 1024 nodes. The paper considers Arduino nano for collecting data using a 10-bit analog-digital converter (ADC) [ 11 ]. The data acquisition was done considering six sleeping postures from five participants, with the convolutional neural networks implemented on a PC.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The JS algorithm belongs to swarm optimisation methods which are inspired by biosystems from nature. Swarm algorithms are very popular in practical (real-world) applications in various areas of research, industry and healthcare services [7,15].…”
Section: Introductionmentioning
confidence: 99%